Two Elongation Responses to Auxin Respond Differently to Protein Synthesis Inhibition - Vanderhoef, Larry N. (1976)
The first and second responses to auxin react differently to the inhibition of protein synthesis by cycloheximide. It was determined that the protein with the shortest half-life, among the several necessary for the first response, is different from its counterpart among the several necessary for the second response. Specifically, the protein half-lives are 28 minutes and 11 minutes for the first and second responses, respectively.